2016
DOI: 10.1021/acs.joc.6b01917
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biophysical Investigations of Oligonucleotides Containing Galactose-Modified DNA, LNA, and 2′-Amino-LNA Monomers

Abstract: Galactose-modified thymidine, LNA-T, and 2'-amino-LNA-T nucleosides were synthesized, converted into the corresponding phosphoramidite derivatives and introduced into short oligonucleotides. Compared to the unmodified control strands, the galactose-modified oligonucleotides in general, and the N2'-functionalized 2'-amino-LNA derivatives in particular, showed improved duplex thermal stability against DNA and RNA complements and increased ability to discriminate mismatches. In addition, the 2'-amino-LNA-T deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In summary, singly- or triply-incorporated galactopyranose moieties induced significantly increased duplex stability relative to the reference duplexes, thus expanding the results reported for galactopyranose-modified carbohydrate moieties attached to the 2′-position of nucleotides via triazole [ 64 ] and amide linkages [ 65 , 66 ]. The data reported herein, in combination with the remarkable exonuclease resistance induced by other N -functionalized 2′-amino-LNA nucleotides [ 63 , 65 ], establish monomers M 2 and M 3 as promising constituents of future RNA-targeting oligonucleotide drugs.…”
Section: Resultsmentioning
confidence: 64%
“…In summary, singly- or triply-incorporated galactopyranose moieties induced significantly increased duplex stability relative to the reference duplexes, thus expanding the results reported for galactopyranose-modified carbohydrate moieties attached to the 2′-position of nucleotides via triazole [ 64 ] and amide linkages [ 65 , 66 ]. The data reported herein, in combination with the remarkable exonuclease resistance induced by other N -functionalized 2′-amino-LNA nucleotides [ 63 , 65 ], establish monomers M 2 and M 3 as promising constituents of future RNA-targeting oligonucleotide drugs.…”
Section: Resultsmentioning
confidence: 64%
“…2′,4′-BNA/LNA-S 2 T phosphoramidite 18 was prepared from compound 12 in a manner similar to the synthesis of 7 (Scheme ), although the Vorbrüggen reaction using 2-thiothymine is an alternative for the synthesis of 18 . ,, First, compound 12 was acetylated to give 13 , , which was then converted to 4- O -protected thymidine analogue 14 . 2-Thionation of 14 with Lawesson’s reagent followed by the removal of both 2,6-dimethylphenyl and acetyl groups afforded compound 16 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the 2′-nitrogen is suitable for advanced modifications by various chemical reactions during nucleic acid synthesis. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Previous studies have reported the development of oligonucleotides (ONs), containing 2′-N-substituted ALNA derivatives, such as 2′-N-alkyl, 13,15 2′-N-acyl, 14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] 2′-N-alkoxycarbonyl, 31 and 2′-N-alkylaminocarbonyl. 32 Sensor molecules such as fluorescent dyes, spin labels, and radioisotopes can be incorporated into 2′-amino groups for use as ONs in biological analysis.…”
Section: Introductionmentioning
confidence: 99%